Riesgo y persistencia de las ganancias; Risk and earnings persistence - Juan Fernando Garrido Navia; Jesús-Ancizar Gómez (Revista de Métodos Cuantitativos para la Economía y la Empresa, 2024)
– What can the financial management of small industries and other enterprises, particularly in developing countries, do to reduce their perception of risk to investors? Lowering the beta would allow these companies to access capital at a lower cost, which could have a favorable impact on their valuation. Could financial management do anything to reduce non-diversifiable risk? The aim of this paper is to contribute with new elements to the existing debate as to whether specific or inherent factors of the company can affect the company's non-diversifiable risk, measured by beta. To this end, a balanced and short panel data was built, which has 603 companies listed on Latin American stock exchanges in a relatively short period of time (2016-2021). For Mexican companies, evidence shows the greater the persistence of earnings, the higher the beta. While the adoption of international accounting standards can improve the quality of companies' earnings, this adoption can also affect their market capitalization. Whereas, by economic sector, regardless of the country of origin, it is found that in the banking sector and in the agricultural production sector, the greater the persistence of profits, the lower the risk.
Keywords: G15; G32; 330; Earnings persistence; earnings quality; risk; beta